2020
DOI: 10.31224/osf.io/nrtgb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Filtration Efficiency, Breathability, and Reusability of Improvised Materials for Face Masks

Abstract: There is paucity of data on the performance of different improvised materials to cope with the COVID-19 pandemic. The goal of this study is to evaluate the filtration efficiency and breathability of improvised filtration and commonly available mask materials, as well as to assess their reusability. Materials readily available to the general public such as cotton, fragrance and additive-free dry baby cleaning wipes, and those abundantly available in the hospital setting, such as sterilization wraps, were chosen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The WHO has also urged the research community to actively engage in research to assess effectiveness of various interventions. This has prompted research on materials and approaches to creating face coverings from household materials, and a rapid increase in publications on material choices [ 4 8 ], number of layers [ 4 6 ], attachment mechanisms [ 1 , 9 ], performance during coughing [ 7 , 10 , 11 ], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO has also urged the research community to actively engage in research to assess effectiveness of various interventions. This has prompted research on materials and approaches to creating face coverings from household materials, and a rapid increase in publications on material choices [ 4 8 ], number of layers [ 4 6 ], attachment mechanisms [ 1 , 9 ], performance during coughing [ 7 , 10 , 11 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few of the filtration studies with household materials have been performed under such worst-case testing [ 5 , 6 , 23 ]. Differences in protocols across studies, [ 4 , 5 , 8 , 11 , 24 ] and widely ranging filtration efficiencies for similar materials across various labs [ 4 , 5 , 25 ] make it difficult to interpret results across studies. While surgical masks and fabrics are believed to be source controls [ 26 , 27 ], and are not intended for protecting the wearer, recently, it has been suggested that masks (surgical and face-coverings) can also protect the wearer to some extent by reducing the inoculum of the virus that results in much milder infections [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The (0.58 ± 0.03) kPa m –1 s value measured in the 5% foam indicates high breathability, which is critical for face mask viability, as compared to that of 1.0 kPa m –1 s for the N95 respirators and 0.86 kPa m –1 s for double-layered high thread count (HTC) cotton cloth filters . For face velocities of about 0.01–0.1 m/s, PD across our foams are in the 6–60 Pa range (i.e., within the breathable range) …”
Section: Filtration Characteristicsmentioning
confidence: 72%
“…36 For face velocities of about 0.01−0.1 m/s, PD across our foams are in the 6−60 Pa range (i.e., within the breathable range). 37 Filtration properties of the synthesized 2ED-Cu foams have been evaluated through two tests. First, a smoke test is performed by burning small white birch wood pellets, generating smoke with PM 2.5 = 4 × 10 6 particles L −1 , PM 10 = 2.5 × 10 4 particles L −1 , and PM +10 = 1.8 × 10 3 particles L −1 , and filtering through two consecutive 5% 2ED-Cu foams.…”
Section: ■ Filtration Characteristicsmentioning
confidence: 99%
“…It has been reported that cotton is the most widely used fabric for mask and higher count cotton offer better filtering efficiency. A comparative analysis of cotton-based masks and surgical masks showed that the penetration efficiency in cotton was 97%, while that in the surgical mask was 45% [46].…”
Section: Types Of Face Masksmentioning
confidence: 99%